Pengaruh Coupon Dan Maturiti Terhadap Tingkat Perubahan Harga Obligasi Korporasi - Juniaty Ismail (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
This research aims to determine the effect of the coupon and maturity period of bonds to the rate of change in the bond price listed on the Indonesia Stock Exchange. The variables used are the Coupon (X1), the Maturity time period (X2) and the bond price change (Y). The samples used were 158 bonds listed on the Indonesia Stock Exchange which were selected purposive sampling. The model used in this study was a double linear regression model. The results of simultaneous research showed that the coupon and maturity period of bonds had no significant effect on the rate of change in bond prices, with a value of F table of 1.00 and Magnitude F Count 0.685. Partially there is no significant influence between the coupon and the maturity period of the bonds to the change in the price of bonds in the Indonesian stock exchange.